Self-confidence in the care of critically ill patients: before and after a simulated intervention - Rodrigo Guimarães dos Santos Almeida; Alessandra Mazzo; José Carlos Amado Martins; Beatriz Maria Jorge; Valtuir Duarte de Souza Júnior; Isabel Amélia Costa Mendes (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To evaluate the self-confidence of nurses in the care of critically ill patients, before and after a simulated intervention. Method: A quasi-experimental study was carried out with 103 nurses who participated in a workshop on the care of critically ill patients in the first semester of 2016. A clinical simulation pedagogical instrument was used throughout the event, and self-confidence was assessed by the Portuguese version of the Self-confidence Scale (SCSvp). Results: Most participants reported not being prepared to provide first care to critically ill patients, which was carried out during care practice. The participants presented a significant increase in self-confidence after the simulated intervention (p<0.001) in the cardiac, neurological, and respiratory dimensions. Conclusion: Simulation has proved to be an effective strategy for the development of individuals' self-confidence, which contributes to the improvement of skills required for professional practice.